Physical, Chemical and Microbial Characteristic of Gouda Cheese Using Propolis (Apis milifera Liguistica) as Coating Material - Lilik Eka Radiati; Muhammad Junus; Khotibul Umam Al Awaly (Faculty of Animal Science Universitas Brawijaya, 2011)
Gouda cheeses were coated with different coating materials consist of pliol, beeswax, and beeswax containing different concentration of propolis by 0,2, 0,4 and 0,8% and stored during ripening at 10oC period. The result showed that no different of moisture, fat and protein content, hardness, pH value of cheese products. The hydrolysis process at maturity caused decreasing of pH value. Added propolis in the coating material could inhibited mould and yeast growth significantly. Key words: Gouda Cheese, propolis, edible coating